PENGEMBANGAN BAHAN AJAR CERITA BERGAMBAR BERBASIS LINGKUNGAN PADA MATERI DISEKITAR RUMAH KELAS I SEKOLAH DASAR - Sri Inggit Rachayu; Ujang Jamaludin; Zeri Rahman Hakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Research and Development (R&D) is motivated by a needs analysis through observation and interviews at Banjarsari 2 Public Elementary School, which shows the need for contextual teaching materials for the material "around the house" in grade 1. The objectives of the research are (1) to describe the process of developing environmental-based picture story teaching materials; (2) to assess the feasibility of the product through expert validation; (3) to describe students' responses to the use of teaching materials. The development model adapts Borg & Gall with six core stages: problem identification, design, development, expert validation, revision, and limited trials. Data were collected through observation, interviews, questionnaires and documentation. Validation involved two material experts, two media experts, and two language experts. The validation results showed an average score of 78.18% and were categorized as "Feasible" based on percentage conversion criteria. Limited trials on grade 1 students resulted in an average response score of 92% with the category "Very Good" indicating high acceptance, understanding, and attractiveness. The conclusion is that the environmental-based picture story teaching material on the material around the house is in the appropriate and very good category for use as teaching material on the material around the house for the Indonesian Language subject for grade I.